Minimally Invasive Therapies for Female Stress Urinary Incontinence: the Current Status of Bioinjectables/New Devices (Adjustable Continence Therapy, Urethral Submucosal Collagen Denaturation by Radiofrequency). (2009) - Crivellaro, Simone; Smith, John J.
Abstract : The aim of this review is to provide an update on the current status of evolving minimally invasive therapies for stress urinary incontinence. Bioinjectables have been available for some time and their current status is reviewed. The adjustable continence device has been used as a salvage procedure for females for a number of years in clinical trials, yet many are unfamiliar with it. Lastly, radiofrequency via a transurethral route has also been utilized in small numbers and will be updated. These later two emerging technologies need further exposure to better define their role in our clinical practice.